DETERMINANTS OF FOOD INSECURITY AMONG YAM- FARMING HOUSEHOLDS IN WUKARI LOCAL GOVERNMENT AREA OF TARABA STATE, NIGERIA - Olayiwola, S. A.; Ibe, A. A.; Yakubu, D.; Olayiwola, M. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This Study examined the determinants of food insecurity incidence among yam farming households in Wukari Local Government Area of Taraba State, Nigeria. Multistage sampling technique was used to arrive at the sampling of 220 respondents in the study area. Data were collected using structured questionnaire and analyzed using descriptive statistics, Foster Greer and Thorbeck (FGT) and probit regression. The results showed that 66.4% of the respondents were male with a mean age of 49years, 51.8% of the respondents had a household size of 1-5 persons, 38.2% of the respondents acquired secondary education. The monthly expenditure for household consumption was used to establish food security line. A mean per capita monthly consumption expenditure of ₦13,100.6 with food insecurity line of ₦8,733.6 was used to classify the households, survey found 54.5% of the respondents to be food insecure. It further revealed a food insecurity incidence of 72.5%, food insecurity depth of 9.2% and food insecurity of 18.3%. The probit regression analysis showed that the coefficients of farming experience (X1), farm size (X4), educational status (X5) and age (X6) were significantly influenced on food insecurity. Coping strategies adopted showed that Withdrawal of children from school ranked 1st with a mean score of (3.75), harvesting immature food crop was ranked 2nd with mean score of (3.57), Selling durable assets ranked 3rd with a mean score of (3.40), Eating once a day is ranked 4th with a mean score of (3.31). It was concluded that majority of the respondents were found to be food insecure and various coping strategies were adopted to reduce food insecurity incidence. Farmers should be encouraged by providing incentives such as grants, loan, improved seeds, machineries and pesticides.